Development of a constitutive model for friction in bulk metal forming - Lüchinger, Marco; Velkavrh, Igor; Kern, Kerstin; Baumgartner, Michael; Klien, Stefan; Diem, Alexander; Schreiner, Michael; Tillmann, Wolfgang (Technische Universität Dortmund, 2018)
This paper presents a systematic procedure for the development of a constitutive model of friction with focus on the application in bulk metal forming simulations. The empirically based friction model describes friction as a function of sliding distance and the most relevant friction influencing parameters. The latter were determined by means of designed experiments. An optimal friction model is obtained as a trade-off between model accuracy and complexity by using stepwise nonlinear regression and a modified version of the Akaike information criterion. Within this study, the procedure is applied to determine a friction model for tube drawing. However, the same approach can also be used for modeling friction of any other bulk metal forming process.
Lubricants;Jg. 6, Heft 2 | S. 42-1-42-12
Keywords: Friction; Bulk metal forming; Mathematical modeling; Design of experiments; Stepwise regression; Akaike information criterion; 620; 670; Reibung; Blechumformen; Mathematische Modellierung; Versuchsplanung